Validation of the Substance Abuse Scale of the Personal and Relationships Profile. (9th November 2021) - Lee, Kerry A; Hayward, R Anna; Sacco, Paul
Abstract: There have been limited measurement studies of the substance abuse scale of the Personal and Relationships Profile (PRP) and the impact of social desirability on alcohol and drug use reporting. This study aimed to (a) model the factor structure of the eight-item substance abuse scale of the PRP and (b) examine the relationship of substance use factors with sociodemographic variables—race, income, age, marital status—and social desirability on substance use reporting among a sample of low-income fathers. The study included secondary data analysis of 665 fathers, who participated in a fatherhood program between 2011 and 2015. The two-factor model with the addition of two error covariances exhibited acceptable fit to the data. Sociodemographic characteristics were significantly associated with alcohol and drug use among the sample with social desirability being the strongest predictor of lower alcohol and drug use reporting. Findings suggest that alcohol and drugs are distinct constructs that should be assessed separately, despite being correlated. In social work practice and research, the influence of social desirability in reporting should be accounted for when assessing substance use.